Integrating National Security Values into the Christian Education Curriculum to Support Indonesia's Golden Generation Vision. - Roce Marsaulina; Gilbert Timothy Majesty (International Perspectives in Christian Education and Philosophy, 2026)
This article provides a descriptive analysis of the potential for integrating national security values into the Christian education curriculum as a strategic effort to support Indonesia's vision of generating a golden generation by 2045. The research object is the formal Christian education system in Indonesia, encompassing its curriculum, pedagogy, and the overarching goal of character formation. The central problem addressed is the perceived dichotomy between faith-based education and the cultivation of civic responsibility, specifically concerning national security a concept often narrowly associated with the military rather than with social resilience, tolerance, and unity. The objective is to explore how Christian educational values can be systematically aligned with national priorities to produce graduates who are both devout and patriotic. Employing a qualitative descriptive analysis method, this study synthesizes findings from a literature review of Christian education philosophy, national curriculum standards, and policy documents on national security and character education. The main findings reveal a significant convergence between Christian ethical teachings such as love for neighbor, integrity, and peacebuilding and the core values underpinning national security and social harmony, like Bhinneka Tunggal Ika (Unity in Diversity). The synthesis of ideas proposes a conceptual framework where subjects like civic education and religious studies are interwoven to foster a holistic identity. The article concludes that a deliberate integration of national security values, framed as active citizenship and social stewardship, is not only compatible with Christian education but is essential for realizing the resilient, morally grounded human resources needed for Indonesia 2045.